ANALISIS DAERAH POTENSI PRODUKSI PADI DI NTT MENGGUNAKAN K-MEANS CLUSTER - Nurani Vita Christiani (Badan Pusat Statistik Provinsi NTT, 2024)
This research focuses on clustering the potential of rice in East Nusa Tenggara (NTT) using the K-Means Cluster method in 2023. The objective is to identify areas with high potential in rice production, using indicators such as harvested area, rice production, and rice productivity. The analysis results in three clusters: seven regencies with high potential, ten regencies with medium potential, and five regencies with low potential. These findings can be utilized by policymakers in NTT, including the government and other relevant stakeholders, to determine priorities and formulate targeted policies to enhance rice production in regions with varying levels of potential.